Impersonal and Predatory Relations With Child Victims of Sexual Assault: Pedophilic Interest and Early Childhood Abuse - Abulafia, Judith (International journal of offender therapy and comparative criminology, 2020)
Fixated pedophilic sexual attraction is considered to be a major determinant of risk among sex offenders, but there is little empirical evidence regarding its treatment. It was hypothesized that two prominent factors which have emerged in the literature as being present among some sexual offenders, namely, impersonal, narcissistic, and predatory patterns of offending against victims, and experiencing childhood sexual abuse, may be related to specifically to the strength of pedophilic interest. Such a relationship would provide a deeper understanding of the corollaries of pedophilic interest and would suggest targets for treatment. These factors were explored in a sample of 532 sexual offenders who attended the National Centre for Risk Assessment in Israel, and were found to be significantly related to the level of pedophilic interest in the sample. The implications for treatment of high-risk offenders are discussed.